The Role of Resiliency, Spirituality, and Religiosity in Predicting Satisfaction with Life in the Elderly - yousef a'zami; abdollah mo'tamedi; unes doostian; mohammad jalalvand; mohsen farzanwgan (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2012)
This study investigates the role of resiliency, spirituality and religiosity in predicting life satisfaction among the elderly of Baharestan city and also the weight of each of the predictor variables. In this descriptive- correlational research, 280 aged people in Baharestan city are selected based on a multi-stage cluster sampling. For data collections, questionnaires including Connor-Davidson (CD-RIS) resiliency questionnaire, spirituality / religiosity questionnaire by the United States National Institutes of Health, Diener’s Satisfaction with Life Scale (SWLS), and demographic features questionnaire are used. For data analysis, Pearson correlation coefficient and regression equation coefficients are used. Results show that there is a relationship between resiliency, spirituality and religion and life satisfaction. The regression equation coefficients shows that variables including resiliency, spirituality and religiosity are significantly able to predict life satisfaction (p<0/001). The low variance inflation factor (VIF) indicates that the predictor variables are not in-line. The resiliency is one predictor variables of life satisfaction, but it can be a strong predictor variable with the help of spirituality and religion.